Análise estrutural de tubos de concreto armado com resíduo de borracha de pneu - Trentin, Thiago Francisco Silva [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The concrete material has a number of advantages like durability, low permeability, weather resistance and high compressive strength. These qualities have led its application to the rainwater collection, since the pipes are usually buried, and, thus, are subjected to compressive forces and exposed to the action of water. However, the concrete has some limitations, as, for example, low resistance to tensile stress, high self-weight, ease of cracking and a brittle behavior in rupture. Thus, many materials are being studied in order to be used as a new concrete component, seeking to minimize its disadvantages. One of them is the tire rubber residue. This residue is a fibrous material that takes a long time to decompose and increases the amount of trash in landfills, but it may give a greater deformation capacity and also a more effective distribution of stresses to the concrete. Furthermore, the tire rubber residue can provide an increase in energy absorption and a decrease in the propagation of cracks in the hardened state. However several studies show that the inclusion of tire rubber residue in the concrete causes a decrease in the mechanical strength to compression, a decrease in the workability of the mixtures and an increase of the content of entrained air. This work deals with the analysis of the structural behavior of five reinforced concrete pipes: one without the addition of tire rubber residue (designated as TC); two of them with an content of residue equal to 10 kg of residue per cubic meter of concrete (designated as TR 10); and the last two with a quantity of 20 kg per cubic meter of concrete (designated as TR 20). All the pipes had a nominal diameter of 60 cm and an effective length of 150 cm. In order to quantify the strength of the pipes, the diametral compression tests were performed according to the recommendations of the NBR 8890 (ABNT, 2007). The diametral displacements at the hub ...

O concreto é um material que apresenta uma série de vantagens, como, por exemplo, boa durabilidade, baixa permeabilidade, resistência às condições atmosféricas e grande resistência frente aos esforços de compressão. Estas qualidades fizeram com que sua aplicação fosse difundida para a confecção de tubos de concreto destinados à captação e transporte de água da chuva uma vez que estes elementos são normalmente enterrados, e, deste modo, estão sujeitos a esforços de compressão e expostos à ação da água. No entanto, o concreto tem algumas limitações, como, por exemplo, baixa resistência à tração, elevado peso próprio, facilidade de fissuração e um comportamento frágil na ruptura. Assim, novos materiais passaram a ser estudados a fim de se encontrar novos componentes que pudessem minimizar as suas limitações. Um deles é o resíduo de borracha de pneu, que pode proporcionar ao concreto uma maior capacidade de deformação e também uma distribuição mais eficaz das tensões atuantes. Além disso, este resíduo também pode proporcionar um aumento da absorção de energia e uma diminuição da propagação de fissuras no estado endurecido. No entanto, vários estudos mostram que a inclusão de resíduos de borracha no concreto provoca uma diminuição da resistência mecânica à compressão, uma diminuição da trabalhabilidade das misturas e um aumento do teor de ar incorporado. Nesta pesquisa foi feita uma análise do comportamento estrutural de cinco tubos de concreto armado, sendo um deles sem adição de resíduo de borracha (traço TC), dois deles com uma quantidade de resíduos igual a 10 kg de borracha por metro cubico de concreto (traço TR 10) e outros dois com uma quantidade de resíduo de 20 kg de borracha por metro cubico de concreto (traço TR 20). Todos os tubos confeccionados tinham um diâmetro nominal de 60 cm e um comprimento efetivo de 150 cm. Para...
Keywords: Concreto armado; Concreto - Mistura; Pneus; Reaproveitamento (Sobras, refugos, etc.); Concrete -- Moisture